EFFECT OF CONSUMING GUAVA LEAVES (PSIDII FOLIUM) EXTRACT ON THE LEVEL OF BLOOD PROFILE IN TEENAGE GIRLS AT VOCATIONAL HIGH SCHOOL OF PALEBON SEMARANG, INDONESIA - Yulaeka Yulaeka; Ari Suwondo; Titi Suherni; Suharyo Hadisaputro; M.Choirul Anwar (Belitung Nursing Journal, 2017)
Background: Women are at risk of iron-deficiency anemia, especially in teenage girls. One alternative treatment to prevent the occurrence of anemia is to consume guava leaf extract. Objective: To examine the effect of guava leaves extract on changes in blood profile level in teenage girls. Methods: This study was a quasi-experiment with pretest posttest control group design. This research was conducted at SMK Palebon Semarang Indonesia conducted on December 2016 - January 2017. There were 36 samples selected using a purposive sampling, with 18 samples were assigned in the experiment and control group. Blood profiles was measured in the Laboratory of Cito Klinik Setiabudi to see the hemoglobin level, hematocrit level, erythrocyte count, and platelet count. Data were analyzed using Independent t-test. Results: There were significant differences in hemoglobin and thrombocytes levels after given intervention between the experiment and control group with p-value <0.05. However, the intervention has no effect on hematocrit and erythrocytes levels (p>0.05). Conclusion: Guava leaves (Psidii folium) extracts have a significant effect on changes in hemoglobin and thrombocyte levels in teenage girls, but not in the hematocrit and thrombocytes levels. Therefore, it is suggested that guava leaves (Psidii folium) extracts can be an alternative treatment for midwives to prevent the occurrence of anemia in teenage girls.